Design and Characterization of CMOS On-Chip Antennas for 60 GHz Communications - Titz, Diane; Ben Abdeljelil, Fand; Jan, Sebastien; Ferrero, Fabien; Luxey, Cyril; Brachat, Patrice; Jacquemod, Gilles (Společnost pro radioelektronické inženýrství, 2012)
In this paper, we present the design and the measurement of two antennas realized on a 130nm CMOS process. They both radiate in the 60 GHz band and are dedicated to Wireless Personal Area Network (WPAN) applications. The antennas are manufactured within the frame of a multi-wafer project with several surrounding microelectronic circuits. The first antenna is an Inverted-F antenna (IFA). It has a maximum gain of -8 dBi and a -10 dB matching bandwidth of 20%. The second radiator is a meandered dipole. It has a maximum gain of -14 dBi and a -10 dB matching bandwidth of 10%. The challenging measurement of their reflection coefficient and their gain radiation pattern are presented. Simulated versus measured curves are analyzed. We especially demonstrate the necessity to take into account the closest microelectronic circuits of the antennas for accurate modeling of the radiating performance of 60 GHz on-chip dies.
Keywords: 60 GHz communications; On-Chip antennas; Mm wave radiation pattern set-up.